Demographic characteristics of MS patients in Poland's upper Silesia region - Pierzchala, Krystyna; Adamczyk-Sowa, Monika; Dobrakowski, Pawel; Kubicka-Baczyk, Katarzyna; Niedziela, Natalia; Sowa, Pawel (International journal of neuroscience, 2015)
Objectives: In Poland, no national registry of MS patients has yet been introduced. So far, no demographic studies have been conducted in patients with MS in Upper Silesia. The aim of the present study was to evaluate, for the first time, a selected demographic and clinical parameters in MS patients from the Upper Silesia region and compare these characteristics with previously published data from other regions of Poland. Materials & Methods: 640 patients with clinically defined MS, were prospectively and randomly selected for the study. Social, socio-economic, and demographic data were obtained through a questionnaire study. All subjects performed a self-assessment of their health condition using EQ-5D and EQ-VAS version questionnaires. Results: The ratio of women to men was 2.18. The average age of onset was 29.6 ± 11.1 years; the disease duration was 7.9 ± 4.5 years. The relapsing-remitting form of MS was diagnosed in 73.12%. In 71.25% the onset was monofocal and in 28.75% multifocal disease onset was observed. Among the studied population 339 (52.97%) patients were still employed. A mean EQ-VAS score of 66.11 ± 20.12 was calculated. Conclusions: Results from our study identify for the first time the demographic and clinical characteristics of the Upper Silesia MS population.